Frequency and determinants of vitamin D deficiency among premenopausal and postmenopausal women in Karachi Pakistan - Shamsi, Uzma (BMC Womens Health, 2021)
BACKGROUND: Vitamin D deficiency is becoming a serious public health problem, even in sun-drenched cities like Karachi, Pakistan. We investigated the prevalence of vitamin D deficiency and its association with sociodemographic characteristics, anthropometric measures, and lifestyle factors among premenopausal and postmenopausal women (n = 784). METHODS: Face-to-face interviews were conducted to collect information and serum concentrations of 25-hydroxyvitamin D were measured after the interviews. RESULTS: A total of 57% of women were vitamin D deficient with higher vitamin D deficiency found among premenopausal women (64.7%) compared to postmenopausal women (49%). The median serum concentrations of 25-hydroxyvitamin D (IQR) were 16.7 ng/ml (IQR 9.8–30.0). Factors associated with vitamin D deficiency were lower socioeconomic status (OR 2.00; 95% CI 1.15–3.48), younger age with highest vitamin D deficiency found in < 35 years of age group (OR 3.11; 95% CI 1.76–5.51), and winter season (OR 1.51, 95% CI 1.07–2.15) after adjusting for multiple confounders. The use of vitamin D supplement (OR 0.59, 95% CI 0.38–0.92) and vigorous exercise (OR 0.20, 95% CI 0.05–0.80) were protective against vitamin D deficiency. CONCLUSIONS: The study shows a high prevalence of vitamin D deficiency, with detrimental health effects, among younger women belonging to lower socioeconomic status and during the winter season. The use of vitamin D supplements and vigorous exercise were protective measures. Public health campaigns are needed for education and awareness about vitamin D deficiency to improve vitamin D status for younger women living in poor environments. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12905-021-01339-9.